Social Preferences, Trust, and Communication when the Truth Hurts - Jonathan Gehle; Ferdinand A. von Siemens (CESifo GmbH, 2024)
We investigate how heterogeneous social preferences affect the communication of painful information in social relationships. We characterize the existence conditions for a pooling equilibrium in which individuals conceal painful information because revealing the latter would signal that they are selfish, thereby leading to a loss of trust. We also find that compassionate individuals may then be more tempted to reveal bad news than selfish individuals because they benefit less from an intact social relationship. Moreover, there may be multiple equilibria with different degrees of information disclosure and standard equilibrium refinements have no bite. Coordination on an inefficient equilibrium could therefore lead to severe information frictions, even if the pain of receiving bad news is quite small.
Keywords: D82; D83; D91; 330; communication; painful information; social preferences; trust